Determination of Streptococcus sp. and Candida albicans in the oral cavity of patients undergoing bone marrow transplantation - Bachmeier, Evelin; Goitea, María Elena Migueles; Linares, Jorge Alberto; Wietz, Fernando Martín; Jarchum, Sol; Jarchum, Gustavo; Brunotto, Mabel Noemí; Mazzeo, Marcelo Adrián (Journal of Oral Research, 2021)
Introduction: Chemotherapy can lead to an imbalance in the ecosystem of the oral cavity, allowing the development of mucositis in the immunosuppression phase due to interaction with microbial agents. The objective of this study was to identify bacterial and fungal species that contribute to oral complications in patients undergoing marrow trans-lantation and compare their susceptibility to various antimicrobial agents before and during the immunosuppression period. Material and Methods: This observational-longitudinal study was performed on 18 patients undergoing bone marrow transplantation from the Oncohematology Service of Sanatorio Allende (2018/2019), with buccal mucosa swabs before treatment (I) and mid-stage (M), fourteen days after transplantation. The samples were cultured in selective media for Streptococcus and fungal species and a susceptibility study was performed on Müller Hinton agar. Results: At (I), 82.30% of patients were found to be positive for Streptococcus mutans , 11.30% for Streptococcus salivarius, 5.50% for Streptococcus sobrinus and 9.40% grew mixed commensal microorganisms. At (M), 96.60% were positive for Streptococcus mutans and 23.10% for Streptococcus salivarius, without any growth of Streptococcus sobrinus or mixed microorganisms. In (I), a 27.00% incidence of Candida albicans was observed, while in (M) the incidence was 73.00%. The antibiotics to which the microorganisms were most sensitive in (I) were vancomycin (88.80%), amikacin (83.30%), amoxicillin + clavulanic acid (78.00%), ciprofloxacin (77.75%) and azithromycin (66.60%). In (M) sensitivity to amikacin was 92.30%, vancomycin, 76.90%; amoxicillin + clavulanic acid, 38.50%; azithromycin, 23.10%; and ciprofloxacin, 15.40%. A statistically significant prevalence of Streptococcus mutans was observed in comparison to other species. Conclusion: During the immunosuppression period, there was a significant increase in Candida albicans. The antibiotics to which the bacteria were most sensitive were amikacin and, to a lesser extent, vancomycin, showing significant resistance to ciprofloxacin, azithromycin and amoxicillin + clavulanic acid.